Perancangan Modifikasi Alat Antropometri sebagai Solusi Ketepatan Pengukuran Berbasis Sensor Ultrasonik - Jelika Pamula Hapsari; Yayu Lestari; Sahrul Nur Rohman; Alfan Al Farisi; Nunik Angelia (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to create a modification of a baby anthropometric measuring tool including sensor-based measurements of the baby's length and weight as well as a head circumference measuring tool contained in one tool. 4 students from the Nursing Science and Electrical Engineering study programs participated in the development of this anthropometric tool with a sample of toddlers at the Integrated Service Post as a trial of the tool. This research uses a Research and Development (R&D) method approach. The tool used uses an electronic circuit based on an ultrasonic sensor and an Arduino nano microcontroller. This tool works automatically by connecting it to a power source then pressing the start button located outside the box marked by the monitor screen saying MODAS Baby as a sign that the test will start. When the sample is in the MODAS Baby box according to the procedure, this tool will automatically calculate the baby's length and weight. While waiting for the results to come out, you can measure the head circumference which is right under the baby's head. The results of the baby's body length and weight measurements are displayed on the LCD located on the surface of the box